2015
DOI: 10.1103/physreve.91.032128
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model for the finite-time thermodynamics of small heat engines

Abstract: We study a molecular engine constituted by a gas of N∼102 molecules enclosed between a massive piston and a thermostat. The force acting on the piston and the temperature of the thermostat are cyclically changed with a finite period τ. In the adiabatic limit τ→∞, even for finite size N, the average work and heat reproduce the thermodynamic values, recovering the Carnot result for the efficiency. The system exhibits a stall time τ* where the net work is zero: for τ<τ* it consumes work instead of producing it, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…We here adopt a well-used approximation that with given position of the walls and particle number the particles are in equilibrium [28,29]. If the equilibration of particles is much faster than the dynamics of the walls and the exchange of particles with the baths, the above approximation is justified.…”
mentioning
confidence: 99%
“…We here adopt a well-used approximation that with given position of the walls and particle number the particles are in equilibrium [28,29]. If the equilibration of particles is much faster than the dynamics of the walls and the exchange of particles with the baths, the above approximation is justified.…”
mentioning
confidence: 99%
“…For this system there are multiple valid approaches: for example the one particle gas approach [7] and its legacy [8][9][10][11], the explicit-friction formulae approach [12][13][14], and the gas particles-average approach [15][16][17][18]. Among those references [15] is particularly interesting: there, the authors assumed that (i) the gas is perfect and 1-dimensional; (ii) the piston and each gas particle undergoes elastic collisions, so work is the energy exchanged in this way; (iii) the velocity of a gas particle is randomly changed according to the Maxwell-Boltzmann distribution of the reservoir when reservoir-gas particle collisions occurs [19] and heat is the change in energy of the gas; (iv) the gas distribution is always Maxwellian although gas-reservoir and gas-piston collisions change the temperature of the gas over time. Combined in a laborious averaging process, the authors where able to derive a set of dynamical equations for the time evolution of the gas temperature T and piston position x according to any externally prescribed change of the external force Θ and reservoir temperature Ω.…”
Section: Introductionmentioning
confidence: 99%
“…Combined in a laborious averaging process, the authors where able to derive a set of dynamical equations for the time evolution of the gas temperature T and piston position x according to any externally prescribed change of the external force Θ and reservoir temperature Ω. In [20] we showed with the multiple scales method [21][22][23][24] and some technical assumptions, (discussed in Section II) that the equations derived in [15] allows to find an approximated expression for the heat exchanged with the reservoir in two physically relevant cases: the relaxation to equilibrium and the slow isothermal compression. In the same paper [20] we pointed out the existence of particular solutions, which we called dynamical equilibrium solutions, which describe the asymptotic behavior of the system when externally driven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system at its ends interacts with thermal baths at fixed temperatures. It is easy to realize the analogy between such a generalized piston model and the systems of masses and springs: the pistons and the gas compartments play the role of masses and springs, respectively.Our model is an example of partitioning system (as the adiabatic piston), where previous studies showed that the presence of mobile walls can induce interesting behaviours [12][13][14][15][16][17][18][19][20][21]. Basically, in the study of partitioning systems, one can adopt two approaches: in terms of a Boltzmann equation [14] or introducing effective equations (Langevin-like) for suitable observables derivedà la Smoluchowski, i.e., from an analysis of the collisions particles/walls.…”
mentioning
confidence: 99%